Use of a supercritical fluid treatment to improve switching region in resistive random access memory. (1st June 2022) - Lin, Shih-Kai; Chen, Min-Chen; Chang, Ting-Chang; Lien, Chen-Hsin; Wu, Cheng-Hsien; Lin, Yu-Shuo; Wu, Pei-Yu; Tan, Yung-Fang; Huang, Wei-Chen; Zhang, Yong-Ci; Chou, Sheng-Yao; Wu, Chung-Wei; et al.
Abstract: This work investigates the influence of a supercritical fluid (SCF) treatment on the characteristics of resistive random access memory. A comparison between the experimental results for the device at initial, after the overset process, and after the SCF treatment, shows that the treatment dopes oxygen ions and generates defects in the switching region (SR). Moreover, the changes in the ratio of the components of the SR after the SCF treatment improve memory characteristics, including a lower set/reset voltage ( V SET / V RESET ), and higher resistances at low resistance state and high resistance state.